The patient's subjective attitude towards screening for breast cancer. Should screening be extended to other forms of cancer?. Issue 660 (October 1980) - Taylor, T. V.; Rimmer, S.; Forrest, A. P.
Abstract : A sample of 500 consecutive women without symptoms of breast disease attending a breast screening clinic were investigated regarding their attitude to breast screening and to the extension of the screening programme to other forms of cancer. Attendance at the screening clinic was found to be reassuring by 94.2%, and 96.4% felt that the screening programme should be extended to include other forms of malignancy. There was a history of either respiratory or alimentary tract symptoms, and of smoking, or a family history of cancer in 41% of these women. The study shows that Edinburgh women are enthusiastic for breast screening and for its extension to include other forms of cancer.